2014
DOI: 10.1021/es501342j
|View full text |Cite
|
Sign up to set email alerts
|

Profile Sampling To Characterize Particulate Lead Risks in Potable Water

Abstract: Traditional lead (Pb) profiling, or collecting sequential liters of water that flow from a consumer tap after a stagnation event, has recently received widespread use in understanding sources of Pb in drinking water and risks to consumer health, but has limitations in quantifying particulate Pb risks. A new profiling protocol was developed in which a series of traditional profiles are collected from the same tap at escalating flow rates. The results revealed marked differences in risks of Pb exposure from one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
103
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(108 citation statements)
references
References 28 publications
4
103
1
Order By: Relevance
“…A number of studies have indicated that significant contributions of particulate-associated lead can be mobilized as a function of flow rate and turbulence in certain water chemistries [94][95][96][97]. Lead-selective ISE sensors are not capable of detecting particulate lead.…”
Section: Detection Of Bound and Particulate Lead In Drinking Watermentioning
confidence: 99%
“…A number of studies have indicated that significant contributions of particulate-associated lead can be mobilized as a function of flow rate and turbulence in certain water chemistries [94][95][96][97]. Lead-selective ISE sensors are not capable of detecting particulate lead.…”
Section: Detection Of Bound and Particulate Lead In Drinking Watermentioning
confidence: 99%
“…Exactly how particulate lead is formed and released to water is relatively poorly understood, and quantification of this problem is highly sensitive to nuances of sampling, including the flow rate during sampling (Reiber et al, 1997;Triantafyllidou and Edwards, 2012;Clark et al, 2014). Obviously, the durability and adherence of lead rust/scale to pipes is one key factor, although as a practical matter little is known about factors that control these characteristics (McNeill and Edwards, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of heavy metals monitoring, it's very important to take into account the accumulation of them in human organisms. That is why monitoring of heavy metals should be carried out in accordance with other principles which take into account the process of metal accumulation in consumer organisms [14][15][16][17][18][19][20][21][22]. The approach to this problem in Poland is fundamentally different from the proper approach, which may give a true picture of water quality in the network.…”
Section: Introductionmentioning
confidence: 99%
“…Water supply companies and sanitary inspection focus only on aspects shown if water quality meets the guidelines outlined in the Regulation of the Polish Minister of Health, the frequency and optimal localization of monitoring points aren't important for them. [15,19,21,22]. In the United States, the EPA recommends an individual approach to monitoring of heavy metals for which separate recommendations have been made.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation